Holden Caulfield’s Juvenile Delinquency Acts Motives in The Catcher in the Rye - Rikha Rizanatul Afiyah (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2017)
This thesis is entitled “An Analysis on the Motives of Juvenile Delinquency Acts Committed by Holden Caulfield in The Catcher in the Rye Novel”. The objectives of this study are to find the motives of juvenile delinquency acts committed by Holden Caulfield and to analyze the aspects of teenage education in the juvenile delinquency acts committed by Holden Caulfield. The writer used descriptive – qualitative method to analyze the novel which is needed to be analyzed by words since the aim of this study is to find the motives of juvenile delinquency acts committed by Holden Caulfield and analyze the aspects of teenage education in the juvenile delinquency acts committed by Holden Caulfield. Based on the analysis that has been done, there are five motives which lead Holden Caulfield to do juvenile delinquencies. The motives are caused of physiological need, safety need, belonging and love need, esteem need, and the last one is the self – actualization need. From all the motives that mentioned above, the belonging and love need is the strongest motive for Holden to do juvenile delinquency. Then, there are also some aspects of teenage education which can be learned from the novel of The Catcher in the Rye by J.D Salinger, such as in the process of growing up, parents should pay attention to teenagers’ way of thinking, and consider their attitudes in facing the problems that sometimes occur.The introduction for basic knowledge of norms, laws, and religion would help them to understand their values in society.